A composite catalyst and its preparation method and application

By using composite catalysts, the problems of low yield, high reaction temperature and many side reactions in musk-T production were solved, and the efficient synthesis of musk-T and the recycling of catalysts were achieved, which reduced production costs and resource waste and improved Product quality and environmental protection.

CN116212895BActive Publication Date: 2024-12-24SHANDONG NHU PHARMA +1
View PDF 13 Cites 0 Cited by

Patent Information

Application Number
CN202310223502.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-09
Publication Date
2024-12-24
Estimated Expiration
2043-03-09

AI Technical Summary

Technical Problem

In the prior art, the production of Musk-T has backward technology, small output, low yield, unstable quality, high cost, and difficult catalyst recycling, resulting in environmental protection problems and waste of resources.

Method used

Compound catalysts are used, composed of active metals, support and alcohol amine compounds, and sintered and dried by preparation method to form a highly active catalyst, which is used for the depolymerization and cyclization reaction of musk-T, so as to realize the recycling of catalysts and the improvement of product quality. .

Benefits of technology

Improve the yield and selectivity of musk-T, shorten the reaction time, reduce the reaction temperature, inhibit the occurrence of side reactions, reduce production costs, and the catalyst can be recycled and reduce solid waste generation, which is in line with the concept of green environmental protection. .

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116212895B_ABST
    Figure CN116212895B_ABST
Patent Text Reader

Abstract

The present invention relates to a composite catalyst and a preparation method and application thereof, wherein the raw materials for preparing the composite catalyst include at least two metal compounds, a carrier, an alkaline substance and a solvent. The composite catalyst of the present invention has high activity, high selectivity and high conversion rate, effectively shortens the reaction time for preparing musk-T, and improves the reaction yield; the composite catalyst is not easy to deactivate, is simple to separate, can be recycled, and reduces production costs; the composite catalyst is used to prepare musk-T, which can significantly reduce the reaction temperature, so that the depolymerization cyclization reaction is carried out under milder conditions, suppresses the occurrence of side reactions, reduces the generation of high-viscosity polymers, avoids waste of resources, conforms to the development concept of green environmental protection, and is conducive to the industrial production of musk-T.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of musk macrocyclic ester compounds, and in particular to a composite catalyst and a preparation method and application thereof. Background Art

[0002] Musk-T, also known as Kunlun Musk, has a chemical name of 1,4-dioxacycloheptadecane-5,17-dione. It is a colorless or slightly yellow viscous liquid and an important macrolide musk fragrance. Musk-T is a high-grade fixative with a scent type close to that of natural musk. It is non-toxic, has a pure aroma, and has a long-lasting fragrance. It has a good rounding and flavoring effect in blending spices and can be widely used in the preparation of various high-grade flavors, especially in the preparation of various high-grade perfumes, shampoos, and cosmetics.

[0003] The method for synthesizing Musk-T is to synthesize a high-viscosity linear polyester by polycondensation of n-tridecanedioic acid and ethylene glycol, and then depolymerize and cyclize the linear polyester to generate a crude product, which is then refined and purified to obtain the final product. This is the only successfully developed industrial route, as follows.

[0004]

[0005] CN103508997A discloses a method for preparing 1,4-dioxacycloheptadecane-5,17-dione (Musk-T) by catalyzing the reaction of brazilic acid (tridecanedioic acid) and ethylene glycol in the presence of a catalyst isopropyl titanate (IPT). US4803288A discloses a method for preparing brazilic acid ethylene glycol ester (Musk-T), wherein brazilic acid and ethylene glycol are reacted in the presence of dibutyltin oxide. CN1172928C discloses a method for synthesizing a macrocyclic lactone compound, wherein tridecanedioic acid, ethylene glycol and palmitic acid are first subjected to an esterification polymerization reaction, and then a depolymerization cyclization reaction occurs under the catalysis of dibutyltin oxide to generate tridecanedioic acid cycloethylene ester (Musk-T). The catalysts used in the above three methods are difficult to recycle, and the catalysts cannot be recycled and reused, which not only leads to high production costs, but also causes severe environmental problems.

[0006] CN105884742A returns the residual liquid containing dimers and trimers to the depolymerization kettle for re-depolymerization, forming a closed cycle without generating "three wastes". Although this method can increase some products, the recovery is limited. At the same time, a large amount of energy consumption is increased during the recovery process, and the economic benefit ratio is not strong.

[0007] CN111620773A discloses a method for preparing dibasic acid from musk-T still residue, in which zinc salt is used as a catalyst in a strong alkaline environment to depolymerize still residue into tridecanedioic acid, and tridecanedioic acid crystals are obtained after multiple crystallization and washing. However, the strong alkali and dilute acid used in this process will corrode the equipment, and acid-base neutralization will produce a large amount of wastewater and waste liquid, which does not conform to the concept of green chemical industry.

[0008] In the prior art, the production of Musk-T has problems such as backward process technology, small output, low yield, unstable quality, high cost, etc., which seriously restrict the industrial production of Musk-T and its status and scope of use in flavor formulas.

[0009] In the synthesis process of musk-T, the depolymerization and cyclization process is a key step that affects the yield and quality of musk-T products. This step is a reversible reaction and needs to be carried out at high temperature, high vacuum and in the presence of a catalyst. The main difficulty lies in the high viscosity of the reactants and the heat transfer problem. As the product is continuously evaporated, the viscosity of the polyester increases further, the heat transfer resistance increases, and the chain growth reaction rate is accelerated under the action of long-term high temperature, the stirring effect is reduced, and the heat transfer efficiency is reduced, so that local overheating occurs, the material close to the kettle wall is carbonized, and the center of the material cannot reach the depolymerization temperature, which ultimately leads to an increase in by-products, a decrease in the yield of musk-T and a large amount of reactor residue. The reactor residue contains a large amount of high-viscosity polymers. If it is directly treated as solid waste, it will not only increase the post-processing process and cost, but also cause a huge waste of resources.

[0010] Therefore, the key technical point of synthesizing musk-T is to develop a highly active depolymerization and cyclization catalyst and transfer musk-T to the interface in time to promote the reaction equilibrium to move towards the direction of musk-T formation.

[0011] In summary, it is crucial to develop a composite catalyst that can overcome the above-mentioned defects. Summary of the invention

[0012] In view of the deficiencies in the prior art, the present invention aims to provide a composite catalyst and a preparation method and application thereof, wherein the composite catalyst solves the technical problems of low yield, high reaction temperature, and multiple side reactions in the depolymerization and cyclization step in the synthesis process of musk-T, and the composite catalyst can effectively improve the yield and selectivity of musk-T, shorten the reaction time, reduce the reaction temperature, effectively inhibit the occurrence of side reactions, and obtain stable product quality. At the same time, the catalyst can be recycled, production costs can be reduced, and the composite catalyst has a good prospect for industrial application.

[0013] To achieve this object, the present invention adopts the following technical solutions:

[0014] In a first aspect, the present invention provides a composite catalyst, wherein raw materials for preparing the composite catalyst include at least two metal compounds, a carrier, an alkaline substance and a solvent.

[0015] In the present invention, the composite catalyst solves the technical problems of low yield, high reaction temperature, and many side reactions in the depolymerization and cyclization step of musk-T synthesis process. The composite catalyst can effectively improve the yield and selectivity of musk-T, shorten the reaction time, reduce the reaction temperature, effectively inhibit the occurrence of side reactions, and obtain stable product quality. At the same time, the catalyst can be recycled and the production cost can be reduced.

[0016] Preferably, the metal compound comprises a combination of a first metal compound and a second metal compound;

[0017] The metal element of the first metal compound includes any one of ruthenium, palladium or platinum, or a combination of at least two thereof;

[0018] The metal element of the second metal compound includes any one of nickel, iron, copper, titanium or manganese, or a combination of at least two of them.

[0019] Preferably, the first metal compound and the second metal compound each independently include any one of nitrates, hydrochlorides, sulfates, acetates or hydrates thereof of the metal element, or a combination of at least two thereof.

[0020] Preferably, the carrier comprises any one of calcium carbonate, activated alumina, titania, zirconium oxide, niobium pentoxide or ZSM-5 zeolite or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of calcium carbonate and activated alumina, a combination of titania, zirconium oxide and niobium pentoxide, a combination of titania, zirconium oxide, niobium pentoxide and ZSM-5 zeolite, and the like.

[0021] Preferably, the alkaline substance comprises an alcoholamine compound.

[0022] Preferably, the alkaline substance comprises any one of ethanolamine, diethanolamine, triethanolamine, N-methylmonoethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-butyldiethanolamine or N,N-diethylethanolamine, or a combination of at least two thereof, wherein typical but non-limiting combinations include: a combination of ethanolamine and diethanolamine, a combination of triethanolamine, N-methylmonoethanolamine and N-methyldiethanolamine, a combination of N-ethyldiethanolamine, N-butyldiethanolamine and N,N-diethylethanolamine, and the like.

[0023] Preferably, the solvent comprises water.

[0024] Preferably, based on the total mass of the carrier as 100%, the mass of the metal element in the first metal compound is 0.5%-5.0%, for example 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, etc., and more preferably 1.0%-4.0%.

[0025] Preferably, based on the total mass of the carrier as 100%, the mass of the first metal compound is 1.0%-7.0%, for example, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0% and the like.

[0026] Preferably, the mass ratio of the alkaline substance to the carrier is (1-10):1, wherein 1-10 can be 2, 3, 4, 5, 6, 7, 8, 9, etc.

[0027] In a second aspect, the present invention provides a method for preparing the composite catalyst according to the first aspect, the preparation method comprising the following steps:

[0028] (1) mixing at least two metal compounds, a solvent and a carrier, and drying the obtained mixed solution to obtain a solid substance;

[0029] (2) sintering the solid material to obtain a catalyst precursor;

[0030] (3) The catalyst precursor, alkaline substance and solvent are mixed and dried to obtain the composite catalyst.

[0031] Preferably, in step (1), the mixing comprises first mixing at least two metal compounds with a solvent and then mixing with a carrier.

[0032] Preferably, the mixing method includes stirring.

[0033] Preferably, the mixing further includes heat preservation and filtration.

[0034] Preferably, the insulation temperature is 40-60°C, for example, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, etc.

[0035] Preferably, the insulation time is 2-4 hours, such as 2.5 hours, 3 hours, 3.5 hours, etc.

[0036] Preferably, in step (2), the sintering temperature is 400-600°C, such as 450°C, 500°C, 550°C, etc.

[0037] Preferably, the sintering time is 2-4 h, such as 2.5 h, 3 h, 3.5 h, etc.

[0038] Preferably, in step (3), the mixing further includes heat preservation and filtration.

[0039] Preferably, the insulation temperature is 40-60°C, for example, 42°C, 44°C, 46°C, 48°C, 50°C, 52°C, 54°C, 56°C, etc.

[0040] Preferably, the insulation time is 2-4 hours, such as 2.5 hours, 3 hours, 3.5 hours, etc.

[0041] As a preferred technical solution, the preparation method comprises the following steps:

[0042] (1) stirring and mixing at least two metal compounds and a solvent, and then stirring and mixing with a carrier, continuing to stir, and then keeping warm at 40-60° C. for 2-4 hours, and then filtering and drying the obtained mixed solution to obtain a solid substance;

[0043] (2) sintering the solid material at 400-600° C. for 2-4 hours to obtain a catalyst precursor;

[0044] (3) The catalyst precursor, alkaline substance and solvent are mixed and stirred, kept at 40-60° C. for 2-4 hours, and dried to obtain the composite catalyst.

[0045] In a second aspect, the present invention provides a use of the composite catalyst described in the first aspect in the preparation of musk-T.

[0046] In a third aspect, the present invention provides a method for preparing musk-T, the preparation method comprising the following steps:

[0047] (1') reacting tridecanedioic acid and ethylene glycol to obtain polyester;

[0048] (2') heating the polyester and the composite catalyst mixture to cause a depolymerization and cyclization reaction to obtain the musk-T.

[0049] Preferably, in step (1'), the raw materials for the reaction further include a polymerization inhibitor.

[0050] Preferably, based on the total mass of the tridecanedioic acid as 100%, the mass of the composite catalyst is 1.0%-7.0%, for example, 2.0%, 3.0%, 4.0%, 5.0%, 6.0%, 7.0%, etc.

[0051] Preferably, in step (2'), the temperature of the depolymerization and cyclization reaction is 100-200°C, such as 120°C, 140°C, 160°C, 180°C, etc.

[0052] Preferably, the depolymerization and cyclization reaction further includes post-treatment.

[0053] Preferably, the post-treatment comprises distillation.

[0054] In a fourth aspect, the present invention provides a method for recovering the composite catalyst after the preparation method described in the second aspect is completed, and the recovery method comprises the following steps:

[0055] The waste material after the preparation method is completed is dissolved in an alkali solution, filtered and washed to obtain a recovered composite catalyst.

[0056] Preferably, the alkali solution comprises a solvent and sodium hydroxide.

[0057] Preferably, the dissolving temperature is 100-200°C, such as 120°C, 140°C, 160°C, 180°C, etc.

[0058] The composite catalyst provided by the present invention is composed of an active metal, a carrier, and an alcoholamine compound. The alcoholamine compound has N and O coordinated atoms at the same time, and can form metal clusters with the active metal. The metal clusters have good dispersibility, so that the active metal is evenly dispersed on the carrier surface, forming a large number of active sites, so that the catalyst presents high activity; in addition, the alcoholamine compound also strengthens the bonding strength between the load component and the carrier, effectively avoids the loss of the active component, and realizes the recycling of the catalyst. The hydroxyl group in the alcoholamine compound can be combined with the terminal carboxyl group in the polyester molecule to prevent the substrate from further polymerization, inhibit the occurrence of side reactions, effectively reduce the influence of the still residue viscosity on the material heat transfer coefficient, reduce the generation of by-products, not only enhance the raw material utilization rate, but also greatly reduce the generation of solid waste.

[0059] Compared with the prior art, the present invention has the following beneficial effects:

[0060] (1) The composite catalyst of the present invention has high activity, high selectivity and high conversion rate, which effectively shortens the reaction time for preparing musk-T and improves the reaction yield. When the composite catalyst of the present invention is used to prepare musk-T, the yield of the crude product without distillation is above 83.1%.

[0061] (2) The composite catalyst of the present invention is not easy to deactivate, is easy to separate, can be recycled, reduces production costs, and has good industrial application prospects. The composite catalyst of the present invention is recovered after preparing musk-T, and the yield of further catalytic preparation of musk-T is reduced by less than 0.4% compared with the first catalytic reaction.

[0062] (3) The preparation method of musk-T described in the present invention can significantly reduce the reaction temperature, so that the depolymerization and cyclization reaction can be carried out under milder conditions, inhibiting the occurrence of side reactions, reducing the formation of high-viscosity polymers, avoiding waste of resources, complying with the development concept of green environmental protection, and facilitating the industrial production of musk-T. BRIEF DESCRIPTION OF THE DRAWINGS

[0063] Figure 1 is the gas chromatography-mass spectrometry (GC-MS) diagram of the crude musk-T product obtained in Application Example 1;

[0064] Figure 2 is a GC-MS graph of the Musk-T distillation product obtained in Application Example 1;

[0065] Figure 3a is the mass spectrometry result of the Musk-T distillation product obtained in Application Example 1;

[0066] Figure 3b This is the standard spectrum of Musk-T. DETAILED DESCRIPTION

[0067] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0068] Product analysis and testing conditions:

[0069] Agilent GC-MS, model 7890A-5975C;

[0070] Fuli gas chromatograph GC 9790plus, using area normalization method, HP-5 capillary column; model: 30m×0.32mm×0.25μm;

[0071] Column head pressure: 100KPa; injector temperature: 250℃, detector temperature: 280℃; split ratio: 70:1; column flow rate: 1.2mL / min;

[0072] Heating program: 110°C for 10 min, then increase the temperature to 260°C at 40°C / min and hold for 5 min.

[0073] The specific implementation of the present invention is further described below through examples and drawings, but the protection scope of the present invention is not limited to the following examples.

[0074] Polyester was made in the laboratory.

[0075] Metal mass = metal salt mass × metal atomic mass / metal salt molecular weight × 100%;

[0076] Theoretical loading = metal mass / carrier mass × 100%;

[0077] Yield = molar yield of crude musk-T / molar amount of dibasic acid added × 100%.

[0078] The molecular weight of tridecanedioic acid is 244.33; the molecular weight of ethylene glycol is 62.07; and the molecular weight of musk-T is 270.36.

[0079] Unless otherwise specified, other reagents used in the following examples are commercially available; the loading amounts are all theoretical loading amounts.

[0080] 1. Composite catalyst

[0081] Example 1

[0082] This embodiment provides a composite catalyst, wherein raw materials for preparing the composite catalyst include a first metal, a second metal, a carrier, an alkaline substance, and a solvent.

[0083] The composite catalyst is obtained by the following preparation method, which comprises the following steps:

[0084] (1) 0.78 g of ruthenium chloride trihydrate (RuCl 3 ·3H 2 O, molecular weight 261.47), 1.45g anhydrous FeCl3 (molecular weight 162.2) were added to 10mL of purified water, stirred and dissolved, and 10g niobium pentoxide (Nb 2 O 5 ), raise the temperature to 40°C, continue stirring for 3 hours, and filter while hot to obtain a filter cake.

[0085] (2) The filter cake was placed in a muffle furnace, heated to 500° C., calcined for 4 hours, and then cooled to obtain a catalyst precursor.

[0086] (3) 80 g of diethanolamine (DEA) was purified in 100 mL and stirred evenly, then the catalyst precursor was added, the temperature was raised to 50° C., and the mixture was stirred at a constant temperature for 4 hours, then the temperature was lowered and filtered, and the filter cake was placed in an 80° C. drying oven to constant weight to obtain the composite catalyst, 3.0% Ru-5.0% Fe / Nb 2 O 5 -DEA, marked as CAT1#.

[0087] Examples 2-20 and Comparative Examples 1-5

[0088] By changing parameters such as the type and proportion of the first metal, the second metal, the carrier, and the alkaline substance, according to the method of Example 1, Examples 2-20 and Comparative Examples 1-5 provide a composite catalyst, and the composite catalysts are numbered CAT2#-CAT20# and Comparative Example 1#-Comparative Example 5#, respectively. The formula of the raw materials for preparing the composite catalysts is shown in Table 1.

[0089] Table 1

[0090]

[0091]

[0092] Embodiment 21

[0093] This embodiment provides a composite catalyst, wherein raw materials for preparing the composite catalyst include a first metal, a second metal, a carrier, an alkaline substance, and a solvent.

[0094] The composite catalyst is obtained by the following preparation method, which comprises the following steps:

[0095] (1) 0.78 g of ruthenium chloride trihydrate (RuCl 3 ·3H 2 O, molecular weight 261.47), 1.45 g anhydrous FeCl 3 (molecular weight 162.2) was added to 10 mL of purified water, stirred and dissolved, and 10 g of niobium pentoxide (Nb 2 O 5 ), raise the temperature to 50°C, continue stirring for 3 hours, and filter while hot to obtain a filter cake.

[0096] (2) The filter cake is placed in a muffle furnace, heated to 600° C., calcined for 2 hours, and then cooled to obtain a catalyst precursor.

[0097] (3) 80 g of diethanolamine (DEA) was purified in 100 mL and stirred evenly, then the catalyst precursor was added, the temperature was raised to 60° C., and the mixture was stirred at constant temperature for 5 hours, then the temperature was lowered and filtered, and the filter cake was placed in an 80° C. drying oven to constant weight to obtain a composite catalyst with 3.0% Ru-5.0% Fe / Nb 2 O 5 -DEA, marked as CAT21#.

[0098] Embodiment 22

[0099] This embodiment provides a composite catalyst, wherein raw materials for preparing the composite catalyst include a first metal, a second metal, a carrier, an alkaline substance, and a solvent.

[0100] The composite catalyst is obtained by the following preparation method, which comprises the following steps:

[0101] (1) 0.78 g of ruthenium chloride trihydrate (RuCl 3 ·3H 2 O, molecular weight 261.47), 1.45 g anhydrous FeCl 3 (molecular weight 162.2) was added to 10 mL of purified water, stirred and dissolved, and 10 g of niobium pentoxide (Nb 2 O 5 ), raise the temperature to 60°C, continue stirring for 2 hours, and filter while hot to obtain a filter cake.

[0102] (2) The filter cake was placed in a muffle furnace, heated to 500° C., calcined for 4 hours, and then cooled to obtain a catalyst precursor.

[0103] (3) 80 g of diethanolamine (DEA) was purified in 100 mL and stirred evenly, then the catalyst precursor was added, the temperature was raised to 40° C., and the mixture was stirred at constant temperature for 4 hours, then the temperature was lowered and filtered, and the filter cake was placed in an 80° C. drying oven to constant weight to obtain a composite catalyst with 3.0% Ru-5.0% Fe / Nb 2 O 5 -DEA, marked as CAT22#.

[0104] Embodiment 23

[0105] This embodiment provides a composite catalyst, wherein raw materials for preparing the composite catalyst include a first metal, a second metal, a carrier, an alkaline substance, and a solvent.

[0106] The composite catalyst is obtained by the following preparation method, which comprises the following steps:

[0107] (1) 0.78 g of ruthenium chloride trihydrate (RuCl 3 ·3H 2 O, molecular weight 261.47), 1.45 g anhydrous FeCl 3 (molecular weight 162.2) was added to 10 mL of purified water, stirred and dissolved, and 10 g of niobium pentoxide (Nb 2 O 5 ), raise the temperature to 40°C, continue stirring for 4 hours, and filter while hot to obtain a filter cake.

[0108] (2) The filter cake was placed in a muffle furnace, heated to 500° C., calcined for 4 hours, and then cooled to obtain a catalyst precursor.

[0109] (3) 80 g of diethanolamine (DEA) was purified in 100 mL and stirred evenly, then the catalyst precursor was added, the temperature was raised to 50° C., and the mixture was stirred at constant temperature for 4 hours, then the temperature was lowered and filtered, and the filter cake was placed in an 80° C. drying oven to constant weight to obtain a composite catalyst with 3.0% Ru-5.0% Fe / Nb 2 O 5 -DEA, marked as CAT23#.

[0110] 2. Preparation of Musk-T

[0111] Application Example 1

[0112] This application example provides a method for preparing musk-T, which comprises the following steps:

[0113] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, add 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol in sequence, stir slowly, turn on the heating, and accelerate the stirring after the tridecanedioic acid is completely dissolved. Raise the temperature to 180°C, and react at normal pressure and keep warm until no water is distilled out, which marks the end of the polycondensation reaction. Connect a pressure reducing device (oil pump) to perform vacuum distillation to recover excess ethylene glycol. Quickly add 2.0g of tridecanedioic acid and 6.1g of CAT1# (catalyst concentration is 5.0%) to the above polyester, heat to 140°C, control the vacuum degree at 80-90Pa to keep warm for reaction, and the start of the depolymerization reaction is when a light yellow viscous liquid evaporates. After 4 hours, raise the temperature to 160°C until no material evaporates, cool down, and obtain 121.4g of musk-T, with a calculated yield of 89.8%. Using GC detection, if Figure 1 As shown, the impurities were analyzed.

[0114] After distillation, the finished product of Musk-T was obtained and characterized by GC-MS, such as Figure 2 , Figure 3a and Figure 3b ( Figure 2 is the gas phase spectrum of GC-MS; Figure 3a and Figure 3b (Figure 2) shows the comparison between the mass spectrometry results of the product and the standard spectrum.

[0115] Application Example 2-6

[0116] The amount of composite catalyst, reaction conditions (temperature, vacuum degree) and other parameters were changed, and the remaining operations were the same as those in Application Example 1. The reaction results are summarized in the following table, see Table 2.

[0117] Table 2

[0118]

[0119] Application Example 7

[0120] This application example provides a method for preparing musk-T, which comprises the following steps:

[0121] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 93.2g of ethylene glycol (1.5mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover excess ethylene glycol. 8.6g of CAT2# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and the reaction was kept warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 6 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 115.8g of musk-T crude product, with a calculated yield of 85.7%.

[0122] Application Example 8

[0123] This application example provides a method for preparing musk-T, which comprises the following steps:

[0124] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover excess ethylene glycol. 6.1g of CAT3# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 160°C. The vacuum degree was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 117.9g of musk-T crude product, with a calculated yield of 87.2%.

[0125] Application Example 9

[0126] This application example provides a method for preparing musk-T, which comprises the following steps:

[0127] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT4# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 116.8g of musk-T crude product, with a calculated yield of 86.4%.

[0128] Application Example 10

[0129] This application example provides a method for preparing musk-T, which comprises the following steps:

[0130] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover excess ethylene glycol. 6.1g of CAT5# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 160°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 112.3g of musk-T crude product, with a calculated yield of 83.1%.

[0131] Application Example 11

[0132] This application example provides a method for preparing musk-T, which comprises the following steps:

[0133] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of CAT6# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C, and the vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 124.1g of musk-T crude product, with a calculated yield of 91.8%.

[0134] Application Example 12

[0135] This application example provides a method for preparing musk-T, which comprises the following steps:

[0136] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of CAT7# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 116.9g of musk-T crude product, with a calculated yield of 86.5%.

[0137] Application Example 13

[0138] This application example provides a method for preparing musk-T, which comprises the following steps:

[0139] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT8# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 150°C, and the vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 5 hours, the temperature was raised to 180°C until no material was evaporated, and the temperature was lowered to obtain 119.6g of musk-T crude product, with a calculated yield of 88.5%.

[0140] Application Example 14

[0141] This application example provides a method for preparing musk-T, which comprises the following steps:

[0142] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT9# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C, and the vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 5 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 116.7g of musk-T crude product, with a calculated yield of 86.3%.

[0143] Application Example 15

[0144] This application example provides a method for preparing musk-T, which comprises the following steps:

[0145] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover excess ethylene glycol. 6.1g of CAT10# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 117.5g of musk-T crude product, with a calculated yield of 86.9%.

[0146] Application Example 16

[0147] This application example provides a method for preparing musk-T, which comprises the following steps:

[0148] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT11# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 119.6g of musk-T crude product, with a calculated yield of 88.5%.

[0149] Application Example 17

[0150] This application example provides a method for preparing musk-T, which comprises the following steps:

[0151] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 3.7g of CAT12# (catalyst concentration was 3.0%) was quickly added to the above polyester, and the mixture was heated to 130°C. The vacuum degree was controlled at 80-90Pa and the reaction was kept warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 121.1g of musk-T crude product, with a calculated yield of 89.6%.

[0152] Application Example 18

[0153] This application example provides a method for preparing musk-T, which comprises the following steps:

[0154] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT13# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and the reaction was kept warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 123.7g of musk-T crude product, with a calculated yield of 91.5%.

[0155] Application Example 19

[0156] This application example provides a method for preparing musk-T, which comprises the following steps:

[0157] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT14# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 119.4g of musk-T crude product, with a calculated yield of 87.9%.

[0158] Application Example 20

[0159] This application example provides a method for preparing musk-T, which comprises the following steps:

[0160] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT15# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 117.9g of musk-T crude product, with a calculated yield of 87.2%.

[0161] Application Example 21

[0162] This application example provides a method for preparing musk-T, which comprises the following steps:

[0163] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of CAT16# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 115.8g of musk-T crude product, with a calculated yield of 85.7%.

[0164] Application Example 22

[0165] This application example provides a method for preparing musk-T, which comprises the following steps:

[0166] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT17# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 117.6g of musk-T crude product, with a calculated yield of 87.0%.

[0167] Application Example 23

[0168] This application example provides a method for preparing musk-T, which comprises the following steps:

[0169] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT18# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 6 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 118.4g of musk-T crude product, with a calculated yield of 87.6%.

[0170] Application Example 24

[0171] This application example provides a method for preparing musk-T, which comprises the following steps:

[0172] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT19# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa to keep the mixture warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 119.5g of musk-T crude product, with a calculated yield of 88.4%.

[0173] Application Example 25

[0174] This application example provides a method for preparing musk-T, which comprises the following steps:

[0175] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT20# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 118.8g of musk-T crude product, with a calculated yield of 87.9%.

[0176] Application Example 26

[0177] This application example provides a method for preparing musk-T, which comprises the following steps:

[0178] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT21# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum degree was controlled at 80-90Pa and the reaction was kept warm. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 118.8g of musk-T crude product, with a calculated yield of 87.9%.

[0179] Application Example 27

[0180] This application example provides a method for preparing musk-T, which comprises the following steps:

[0181] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT22# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 120.6g of musk-T crude product, with a calculated yield of 89.2%.

[0182] Application Example 28

[0183] This application example provides a method for preparing musk-T, which comprises the following steps:

[0184] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of CAT23# (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. The depolymerization reaction began when a light yellow viscous liquid evaporated. After 4 hours, the temperature was raised to 160°C until no material evaporated, and the temperature was lowered to obtain 121.1g of musk-T crude product, with a calculated yield of 89.6%.

[0185] Application Example 29

[0186] This application example provides a method for preparing musk-T, which comprises the following steps:

[0187] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover excess ethylene glycol. 8.6g of CAT24# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid was evaporated, the depolymerization reaction began. After 6 hours, the temperature was raised to 180°C until no material was evaporated, and the temperature was lowered to obtain 121.0g of musk-T crude product, with a calculated yield of 89.5%.

[0188] Application Example Comparative Example 1

[0189] This application comparative example provides a method for preparing musk-T, which comprises the following steps:

[0190] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of comparative example 1# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid was evaporated, the depolymerization reaction began. After 6 hours, the temperature was raised to 180°C until no material was evaporated, and the temperature was lowered to obtain 93.8g of musk-T crude product, with a calculated yield of 69.4%.

[0191] Application Example Comparative Example 2

[0192] This application comparative example provides a method for preparing musk-T, which comprises the following steps:

[0193] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of comparative example 2# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C, and the vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid was evaporated, the depolymerization reaction began. After 6 hours, the temperature was raised to 180°C until no material was evaporated, and the temperature was lowered to obtain 33.4g of musk-T crude product, with a calculated yield of 24.7%.

[0194] Application Example Comparative Example 2

[0195] This application comparative example provides a method for preparing musk-T, which comprises the following steps:

[0196] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on, and the stirring was accelerated after the tridecanedioic acid was completely dissolved. The mixture was heated to 180°C, and the mixture was kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 8.6g of comparative example 3# (catalyst concentration was 7.0%) was quickly added to the above polyester, and the mixture was heated to 140°C, and the vacuum degree was controlled at 80-90Pa to keep warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 5 hours, the temperature was raised to 180°C until no material evaporated, and the temperature was lowered to obtain 21.1g of musk-T crude product, with a calculated yield of 15.6%.

[0197] Application Example Comparative Example 3

[0198] The difference between this comparative example and Application Example 1 is that CAT1# is replaced by Comparative Example 4#, and the rest is the same as Application Example 1, and 108.7 g of crude musk-T is obtained, and the calculated yield is 80.4%.

[0199] Application Example Comparative Example 4

[0200] The difference between this comparative example and application example 1 is that CAT1# is replaced by comparative example 5#, and the rest is the same as application example 1, and 102.2 g of crude musk-T is obtained, and the calculated yield is 75.6%.

[0201] In summary, when the composite catalyst of the present invention is used to prepare musk-T, the yield of the crude product without distillation is above 83.1%.

[0202] 3. Recycling of composite catalyst

[0203] The method for recovering the catalyst used in Application Example 1 is as follows:

[0204] Add 5.0 g of sodium hydroxide to 100 mL of purified water, stir to dissolve, then add the scraps from Application Example 1, raise the temperature to 140°C, and filter while hot after the scraps are completely dissolved to obtain a catalyst solid, which is then washed three times with purified water to obtain a recovered catalyst.

[0205] The reaction process of Application Example 1 was repeated, and the reaction conditions and operations were the same as those of Application Example 1.

[0206] In a 500mL three-necked flask equipped with an electric stirrer, a thermometer, and a fractionating column, 122.2g of tridecanedioic acid (0.5mol), 124.2g of ethylene glycol (2.0mol), and 2.4g of ethanol were added in sequence, and the mixture was stirred slowly. The heating was turned on. After the tridecanedioic acid was completely dissolved, the stirring was accelerated, and the mixture was heated to 180°C. The mixture was reacted under normal pressure and kept warm until no water was distilled out, which marked the end of the polycondensation reaction. A decompression device (oil pump) was connected to perform decompression distillation to recover the excess ethylene glycol. 6.1g of the recovered catalyst (catalyst concentration was 5.0%) was quickly added to the above polyester, and the mixture was heated to 140°C. The vacuum was controlled at 80-90Pa and kept warm for reaction. When a light yellow viscous liquid evaporated, the depolymerization reaction began. After 6 hours, the temperature was raised to 180°C until no material was evaporated, and the temperature was lowered to obtain 121.0g of musk-T crude product, with a calculated yield of 89.5%.

[0207] The catalyst effect was compared to the first use, and the reaction yield was reduced by 0.4%. The presumed reason was that the scraps on the catalyst surface covered part of the reaction active sites, causing the catalyst activity to decrease slightly, but it still remained at a relatively high level.

[0208] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. Use of a composite catalyst in the preparation of musk-T, characterized in that: The raw materials for preparing the composite catalyst include at least two metal compounds, a carrier, an alkaline substance and a solvent; The metal compound comprises a combination of a first metal compound and a second metal compound; The metal element of the first metal compound includes any one of ruthenium, palladium or platinum, or a combination of at least two thereof; The metal element of the second metal compound includes any one or a combination of at least two of nickel, iron, copper, titanium or manganese; The alkaline substance includes alcoholamine compounds.

2. The use according to claim 1, characterized in that: The first metal compound and the second metal compound each independently include any one of nitrates, hydrochlorides, sulfates, acetates or hydrates thereof of the metal element or a combination of at least two thereof.

3. The use according to claim 1, characterized in that: The carrier includes any one of calcium carbonate, activated alumina, titanium dioxide, zirconium oxide, niobium pentoxide or ZSM-5 zeolite, or a combination of at least two thereof.

4. The use according to claim 1, characterized in that: The alkaline substance includes any one of ethanolamine, diethanolamine, triethanolamine, N-methylmonoethanolamine, N-methyldiethanolamine, N-ethyldiethanolamine, N-butyldiethanolamine or N,N-diethylethanolamine, or a combination of at least two thereof.

5. The use according to claim 1, characterized in that: The solvent includes water.

6. The use according to claim 1, characterized in that: Based on the total mass of the carrier being 100%, the mass of the metal element in the first metal compound is 0.5%-5.0%.

7. The use according to claim 1, characterized in that: Based on the total mass of the carrier as 100%, the mass of the first metal compound is 1.0%-7.0%.

8. The use according to claim 1, characterized in that: The mass ratio of the alkaline substance to the carrier is (1-10):

1.

9. The use according to claim 1, characterized in that: The composite catalyst is prepared by the following method, which comprises the following steps: (1) mixing at least two metal compounds, a solvent and a carrier, and drying the resulting mixed solution to obtain a solid substance; (2) sintering the solid material to obtain a catalyst precursor; (3) The catalyst precursor, alkaline substance and solvent are mixed and dried to obtain the composite catalyst.

10. The use according to claim 9, characterized in that: In step (1), the mixing includes first mixing at least two metal compounds with a solvent and then mixing with a carrier.

11. The use according to claim 10, characterized in that: The mixing method includes stirring.

12. The use according to claim 10, characterized in that: The mixing further includes heat preservation and filtration.

13. The use according to claim 12, characterized in that: The insulation temperature is 40-60°C.

14. The use according to claim 12, characterized in that: The insulation time is 2-4 h.

15. The use according to claim 9, characterized in that: In step (2), the sintering temperature is 400-600°C.

16. The use according to claim 9, characterized in that The sintering time is 2-4 h.

17. The use according to claim 9, characterized in that: In step (3), the mixing further includes heat preservation and filtration.

18. The use according to claim 17, characterized in that The insulation temperature is 40-60°C.

19. The use according to claim 17, characterized in that: The insulation time is 2-4 h.

20. The use according to claim 1, characterized in that: The composite catalyst is prepared by the following method, which comprises the following steps: (1) After at least two metal compounds and a solvent are stirred and mixed, the mixture is stirred and mixed with a carrier, the stirring is continued, and then the mixture is kept at 40-60° C. for 2-4 hours, and then the obtained mixture is filtered and dried to obtain a solid substance; (2) sintering the solid material at 400-600° C. for 2-4 h to obtain a catalyst precursor; (3) The catalyst precursor, alkaline substance and solvent are mixed and stirred, kept at 40-60° C. for 2-4 h, and dried to obtain the composite catalyst.

21. A method for preparing musk-T, characterized in that: The preparation method comprises the following steps: (1') reacting tridecanedioic acid and ethylene glycol to obtain polyester; (2') mixing the polyester and the composite catalyst, heating them, and causing a depolymerization and cyclization reaction to obtain the musk-T; The composite catalyst is the composite catalyst in the application described in claim 1.

22. The preparation method according to claim 21, characterized in that: In step (1'), the raw materials for the reaction also include a polymerization inhibitor.

23. The preparation method according to claim 21, characterized in that: Based on the total mass of the tridecanedioic acid as 100%, the mass of the composite catalyst is 1.0%-7.0%.

24. The preparation method according to claim 21, characterized in that: In step (2'), the temperature of the depolymerization and cyclization reaction is 100-200°C.

25. The preparation method according to claim 21, characterized in that: The depolymerization and cyclization reaction also includes post-treatment.

26. The preparation method according to claim 25, characterized in that: The post-treatment includes distillation.

Citation Information

Patent Citations

  • 1,4-dioxacycloheptadecane-5,17-diketone and preparation method thereof

    CN103508997A

  • Preparation method of musk-T

    CN105884742A

  • Method for preparing binary acid by using musk-T kettle residues

    CN111620773A

  • Technique for producing compound of macrolide

    CN1172928C

  • Process for producing macrocyclic ester compounds

    US4803288A